Ternary lithium ion battery with high temperature resistance and long service life

By using single crystal nickel NCM material and high-thermal stability electrolyte surface-coated solid electrolyte in lithium-ion batteries, the problem of performance attenuation of lithium-ion batteries in high-temperature environments is solved, and the high-temperature cycling performance and energy of the battery is significantly improved. Density, extends battery life.

CN119275270APending Publication Date: 2025-01-07TIANJIN SPACE POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411430463.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The performance of existing lithium-ion batteries is severely attenuated in high temperature environments, especially the thermal stability of ternary materials is reduced, resulting in low energy density and insufficient cycle life, poor stability of the electrolyte and easy combustion.

Method used

A single crystal nickel NCM material with surface-coated solid electrolyte is used as the positive electrode material, and a high-temperature resistant electrolyte is constructed using a high-thermal stability multi-lithium salt system and a flame-retardant organic solvent, combined with film-forming additives to improve the high-temperature cycling performance of the battery.

Benefits of technology

It significantly improves the high-temperature cycling performance and energy density of lithium-ion batteries, extends the service life of the battery, and improves the thermal decomposition temperature and stability of the battery by modifying the positive electrode material and electrolyte, and has good batch production capacity and consistent performance. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275270A_ABST
    Figure CN119275270A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant long-life ternary lithium ion battery, which belongs to the field of lithium ion batteries, comprises a lithium ion battery positive electrode system, a lithium ion battery negative electrode system and an electrolyte, and is characterized in that the lithium ion battery positive electrode system adopts a single-crystal medium nickel NCM material of which the surface is coated with a solid electrolyte; the electrolyte is a high-temperature-resistant electrolyte and comprises the following components in percentage by mass: 5-20% of a multi-lithium-salt system, 60-85% of a mixed solvent of a nitrile solvent and a carbonic ester solvent and 0.5-20% of a film-forming additive. And by carrying out surface coating modification on the single-crystal ternary material, the thermal decomposition temperature of the positive electrode material is effectively improved, and the high-temperature cycle performance of the lithium ion battery is further improved. And in the aspect of high-temperature electrolyte, the high-temperature cycle performance of the lithium ion battery is effectively improved through construction of a high-thermal-stability multi-lithium-salt system, construction of a flame-retardant organic solvent system and compounding of a film-forming additive. And the prepared high-temperature-resistant long-service-life ternary lithium ion battery has batch production capability and good performance consistency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a high temperature resistant and long life ternary lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high power density, long cycle life, low self-discharge rate and no memory effect. They are the batteries with the highest energy density and the best overall performance in secondary battery technology. After more than 30 years of development, lithium-ion batteries have now occupied the main markets in consumer batteries, energy storage batteries, power batteries and other fields. With the continuous expansion of application scenarios, higher requirements are also placed on the performance of lithium-ion batteries.

[0003] For example, in the military and aerospace fields, high temperature environments are common working conditions; in the oil industry, the maximum operating temperature of the battery is required to reach 200°C; in deep space exploration, the detector will face high temperature environments when operating, such as the sunlit side of the moon reaching 120°C, and the sunlit side of Venus reaching a maximum temperature of 485°C; in the medical field, the sterilization temperature of medical equipment is 135°C and above, and in the electric vehicle field, the temperature inside the new energy vehicle can reach 70°C to 80°C when it is started or when it is driven and placed under the scorching sun. Such high temperature environments are severe tests for the performance and service life of the battery. Therefore, it is crucial to develop lithium-ion batteries that can operate at high temperatures and have long cycle performance.

[0004] At present, the maximum operating temperature of commonly used lithium-ion batteries in China is about 70°C, and in order to ensure the long-term stability of the positive electrode material at high temperature, materials with good thermal stability such as LiFePO4 and LTO are generally selected to assemble the battery. However, the theoretical gram capacity of LiFePO4 and LTO materials is low, resulting in a low energy density of the battery, generally below 140Wh / kg. In response to the demand for high energy density, ternary materials have the advantages of high reversible capacity and good thermal stability, and are ideal positive electrode materials. With the increase of nickel content, the energy density of the battery is gradually increasing, but the thermal stability of the material is gradually decreasing. Therefore, it is necessary to modify the ternary positive electrode material to improve the thermal stability of the material and enhance the high temperature performance of the battery.

[0005] The most widely used electrolyte system in commercial applications is LiPF6 combined with carbonate solution. However, LiPF6 in the electrolyte will decompose at 75°C, and the product PF5 is a strong Lewis acid that tends to react with high DNs organic solvents. In addition, PF5 will also react with the SEI membrane, and the generated HF, RCOF, POF3 and other substances will increase the interface impedance, corrode the current collector, and cause the battery performance to decay rapidly. At the same time, the stability of the carbonate system is poor at high temperatures, and it is easy to burn at high temperatures. Therefore, it is necessary to develop a new type of high-temperature resistant electrolyte to improve the high-temperature performance of lithium-ion batteries through flame-retardant solvents, high-temperature resistant lithium salts and additives. Summary of the invention

[0006] In order to solve the technical problems mentioned in the background technology, the present invention provides a high temperature resistant and long life ternary lithium ion battery.

[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a high-temperature resistant and long-life ternary lithium-ion battery, comprising a lithium-ion battery positive electrode system, a lithium-ion battery negative electrode system and an electrolyte, wherein the lithium-ion battery positive electrode system adopts a single crystal nickel NCM material with a surface coated with a solid electrolyte; the electrolyte is a high-temperature resistant electrolyte, which includes, by mass percentage, 5%-20% of a multi-lithium salt system, 60%-85% of a mixed solvent of a nitrile solvent and a carbonate solvent, and 0.5%-20% of a film-forming additive.

[0008] The nickel NCM material in the single crystal is one of NCM523, NCM622 and NCM712.

[0009] The solid electrolyte is one of an oxide solid electrolyte, a sulfide solid electrolyte and a polymer solid electrolyte.

[0010] The lithium salt in the multi-lithium salt system is two or more of trifluoromethylsulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), and lithium tetrafluoroborate (LiBF4).

[0011] The carbonate solvent is one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the nitrile solvent is one or more of adiponitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, and 3-methoxypropionitrile.

[0012] The film-forming additive is one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sulfonic acid (PS), 1,3-propylene sulfone (PES), diethyl sulfate (DTD), lithium difluorophosphate (LiPO2F2), and propenyl-1,3-sultone (PST).

[0013] The positive electrode system of the lithium ion battery comprises the following components: 90%-95% of single crystal nickel NCM material with a surface coated with a solid electrolyte, 2%-6% of a conductive agent, and 1.5%-5% of polyvinylidene fluoride; the negative electrode system of the lithium ion battery comprises the following components: 90%-95% of a graphite material, 2%-6% of a conductive agent, 1%-4% of sodium carboxymethyl cellulose, and 1%-4% of styrene-butadiene rubber.

[0014] The coating surface density of the positive electrode material is 28-32 mg / cm2 The coating surface density of the negative electrode material is 14-17 mg / cm 2 .

[0015] The advantages and technical effects of the present invention are as follows: In terms of positive electrode materials, the selection of ternary materials can significantly improve the energy density of the battery. In addition, compared with polycrystalline ternary materials, single-crystal ternary materials have better structural stability, which is beneficial to improving cycle stability. By surface coating and modifying the single-crystal ternary materials, the thermal decomposition temperature of the positive electrode material is effectively increased, and the high-temperature cycle performance of the lithium-ion battery is further improved. In terms of high-temperature electrolytes, the high-temperature cycle performance of lithium-ion batteries is effectively improved by constructing a multi-lithium salt system with high thermal stability, a flame-retardant organic solvent system, and compounding film-forming additives. The prepared high-temperature resistant and long-life ternary lithium-ion battery has batch production capabilities and good performance consistency. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The figure is a graph showing the high temperature cycle performance test results of the lithium ion batteries of Example 1 and Comparative Examples 1 and 2.

[0017] Figure 2 This is a graph showing the high temperature cycle performance test results of the lithium ion battery of Example 1. DETAILED DESCRIPTION

[0018] The present invention is further described below in conjunction with examples. The embodiments described in the present invention are only used to help understand the present invention and are not limited to the embodiments cited. Any improvements to the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0019] The high temperature resistant and long life ternary lithium ion battery of the present invention comprises a lithium ion battery positive electrode system, a lithium ion battery negative electrode system and an electrolyte. The lithium ion battery positive electrode system adopts a single crystal nickel NCM material with a surface coated with a solid electrolyte; the electrolyte is a high temperature resistant electrolyte, which comprises, by mass percentage, 5%-20% of a multi-lithium salt system, 60%-85% of a mixed solvent of a nitrile solvent and a carbonate solvent, and 0.5%-20% of a film-forming additive.

[0020] The nickel NCM material in the single crystal is one of NCM523, NCM622 and NCM712.

[0021] The solid electrolyte is one of an oxide solid electrolyte, a sulfide solid electrolyte and a polymer solid electrolyte.

[0022] The lithium salt in the multi-lithium salt system is two or more of trifluoromethylsulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), and lithium tetrafluoroborate (LiBF4).

[0023] The carbonate solvent is one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the nitrile solvent is one or more of adiponitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, and 3-methoxypropionitrile.

[0024] The film-forming additive is one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sulfonic acid (PS), 1,3-propylene sulfone (PES), diethyl sulfate (DTD), lithium difluorophosphate (LiPO2F2), and propenyl-1,3-sultone (PST).

[0025] The positive electrode system of the lithium ion battery comprises the following components: 90%-95% of single crystal nickel NCM material with a surface coated with a solid electrolyte, 2%-6% of a conductive agent, and 1.5%-5% of polyvinylidene fluoride; the negative electrode system of the lithium ion battery comprises the following components: 90%-95% of a graphite material, 2%-6% of a conductive agent, 1%-4% of sodium carboxymethyl cellulose, and 1%-4% of styrene-butadiene rubber.

[0026] The coating surface density of the positive electrode material is 28-32 mg / cm 2 The coating surface density of the negative electrode material is 14-17 mg / cm 2 .

[0027] Example 1 Preparation of single crystal nickel NCM material with solid electrolyte coated on the surface (hereinafter referred to as modified ternary NCM material)

[0028] The precursor Ni X Co Y Mn Z (OH)2 and LiOH were mixed in a molar ratio of 1:1.03 and added to a stirrer for stirring and mixing, and then sintered in a tube furnace under air atmosphere, first heated to 600°C at a heating rate of 3°C / min and kept for 4 hours, then heated to 750°C and kept for 12 hours, and naturally cooled to room temperature after the reaction was complete, to obtain positive electrode material powder.

[0029] LiNO3, Al(NO3)3·9H2O, Ti(OC4H9)4, CHOP and the above-obtained positive electrode material are stirred and mixed in a molar ratio of 1.5:0.4:0.8:3.5:1.2, and the mixed solution is sintered in a tubular furnace, heated to 700°C at a heating rate of 3°C / min and maintained for 6 hours. After the reaction is complete, it is naturally cooled to room temperature, and the positive electrode material coated with a solid electrolyte is obtained after grinding and sieving.

[0030] Example 2 Preparation of high temperature resistant electrolyte

[0031] The high temperature resistant electrolyte includes an organic solvent, a lithium salt and an additive. The lithium salt is a mixed multi-lithium salt system formed by LiTFSI and LiFSI in a mass ratio of 1:2.5. The organic solvent is a mixed system of EC, DMC, EMC and adiponitrile, wherein the mass ratio of adiponitrile and carbonate solvent is 1:19. The additive is a mixed system of FEC, PS, DTD, and LiPO2F2. First, adiponitrile and carbonate solvent are mixed in a mass ratio of 1:19, and then LiTFSI and LiFSI are added thereto. Finally, the additive is added in a mass ratio of FEC:PS:DTD:LiPO2F2=7:3:1:1 for mixing, and the high temperature resistant electrolyte is obtained after stirring evenly.

[0032] Example 3 Preparation of high temperature resistant and long life ternary lithium ion battery

[0033] The positive electrode system is 93% of the modified ternary NCM material prepared in Example 1, 5% of the conductive agent, and 2% of polyvinylidene fluoride. The negative electrode system is 94% of the graphite material, 3% of the conductive agent, 1.5% of sodium carboxymethyl cellulose, and 1.5% of styrene-butadiene rubber.

[0034] The positive electrode material coating surface density is 30 mg / cm 2 The surface density of the negative electrode material is 16 mg / cm 2 .

[0035] The thickness of the aluminum foil is 15 μm, and the thickness of the copper foil is 6 μm.

[0036] The electrolyte used is the high temperature resistant electrolyte prepared in Example 2.

[0037] The battery cell is formed by an automatic cylindrical winding method, and the battery structure is a cylindrical structure.

[0038] The lithium-ion battery prepared according to the above method is subjected to a 75°C high-temperature cycle performance test: the lithium-ion battery is placed in a high and low temperature box, the temperature is set to 75°C, and after the battery body temperature reaches 75°C, a charge and discharge cycle test is performed at a rate of 0.5C charging and 1C discharging.

[0039] Comparative Example 1

[0040] The positive electrode system is 93% unmodified ternary NCM material, 5% conductive agent, and 2% polyvinylidene fluoride.

[0041] The negative electrode system is composed of 94% graphite material, 3% conductive agent, 1.5% sodium carboxymethyl cellulose, and 1.5% styrene-butadiene rubber.

[0042] The positive electrode material coating surface density is 30 mg / cm 2 The surface density of the negative electrode material is 16 mg / cm 2 .

[0043] The thickness of the aluminum foil is 15 μm, and the thickness of the copper foil is 6 μm.

[0044] The lithium salt in the electrolyte is a mixed system of LiTFSI and LiFSI, the organic solvent is a mixed system of EC, DMC, EMC and adiponitrile, and the additive is a mixed system of FEC, PS, DTD, and LiPO2F2.

[0045] The battery cell is formed by an automatic cylindrical winding method, and the battery structure is a cylindrical structure.

[0046] The lithium-ion battery prepared according to the above method is subjected to a 75°C high-temperature cycle performance test: the lithium-ion battery is placed in a high and low temperature box, the temperature is set to 75°C, and after the battery body temperature reaches 75°C, a charge and discharge cycle test is performed at a rate of 0.5C charging and 1C discharging.

[0047] Comparative Example 2

[0048] The positive electrode system is 93% of unmodified ternary NCM material, 5% of conductive agent, and 2% of polyvinylidene fluoride. The negative electrode system is 94% of graphite material, 3% of conductive agent, 1.5% of sodium carboxymethyl cellulose, and 1.5% of styrene-butadiene rubber.

[0049] The positive electrode material coating surface density is 30 mg / cm 2 The surface density of the negative electrode material is 16 mg / cm 2 .

[0050] The thickness of the aluminum foil is 15 μm, and the thickness of the copper foil is 6 μm.

[0051] The lithium salt in the electrolyte is LiPF6, the organic solvent is a mixed system of EC, DMC and EMC, and the additive is a mixed system of FEC, PS, DTD, and LiPO2F2.

[0052] The battery cell is formed by an automatic cylindrical winding method, and the battery structure is a cylindrical structure.

[0053] The lithium-ion battery prepared according to the above method is subjected to a 75°C high-temperature cycle performance test: the lithium-ion battery is placed in a high and low temperature box, the temperature is set to 75°C, and after the battery body temperature reaches 75°C, a charge and discharge cycle test is performed at a rate of 0.5C charging and 1C discharging.

[0054] from Figure 1 It can be seen from the data that the lithium-ion battery prepared in the embodiment of the present invention has a high capacity retention rate under high temperature 75°C cycling, and the capacity retention rate is 94.97% after 100 cycles. The capacity retention rate of the lithium-ion battery prepared in Comparative Example 1 using unmodified ternary positive electrode materials is 91.43% after 100 cycles at 75°C, indicating that the modification of the positive electrode material by the present invention effectively improves the thermal stability of the positive electrode material, thereby improving the high temperature cycle performance of the lithium-ion battery. The capacity retention rate of the lithium-ion battery prepared in Comparative Example 2 using unmodified ternary materials as the positive electrode material and a mixture of LiPF6, carbonate solvents and film-forming additives as the electrolyte is 73.93% after 100 cycles at 75°C, and the battery capacity retention rate has decreased significantly, indicating that the selection of high thermal stability lithium salts and high temperature resistant organic solvents is crucial for lithium-ion batteries to work at high temperatures for a long time.

[0055] from Figure 2 It can be seen from the data that the lithium ion battery prepared in the embodiment of the present invention can maintain a capacity of 80% after about 550 cycles at a high temperature of 75°C, indicating that the lithium ion battery prepared in the present invention has good high temperature cycle performance.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high temperature resistant and long life ternary lithium ion battery, comprising a lithium ion battery positive electrode system, a lithium ion battery negative electrode system and an electrolyte, characterized in that: The positive electrode system of the lithium-ion battery adopts a single crystal nickel NCM material with a solid electrolyte coated on the surface; the electrolyte is a high-temperature resistant electrolyte, which includes 5%-20% of a multi-lithium salt system, 60%-85% of a mixed solvent of a nitrile solvent and a carbonate solvent, and 0.5%-20% of a film-forming additive in terms of mass percentage.

2. The high temperature resistant and long life ternary lithium ion battery according to claim 1, characterized in that: The nickel NCM material in the single crystal is one of NCM523, NCM622 and NCM712.

3. The high temperature resistant and long life ternary lithium ion battery according to claim 1, characterized in that: The solid electrolyte is one of an oxide solid electrolyte, a sulfide solid electrolyte and a polymer solid electrolyte.

4. The high temperature resistant and long life ternary lithium ion battery according to claim 1, characterized in that: The lithium salt in the multi-lithium salt system is two or more of trifluoromethylsulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), and lithium tetrafluoroborate (LiBF4).

5. The high temperature resistant and long life ternary lithium ion battery according to claim 1, characterized in that: The carbonate solvent is one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the nitrile solvent is one or more of adiponitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, and 3-methoxypropionitrile.

6. The high temperature resistant and long life ternary lithium ion battery according to claim 1, characterized in that: The film-forming additive is one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sulfonic acid (PS), 1,3-propylene sulfone (PES), diethyl sulfate (DTD), lithium difluorophosphate (LiPO2F2), and propenyl-1,3-sultone (PST).

7. The high temperature resistant and long life ternary lithium ion battery according to claim 1, characterized in that: The positive electrode system of the lithium ion battery comprises the following components: 90%-95% of single crystal nickel NCM material with a surface coated with a solid electrolyte, 2%-6% of a conductive agent, and 1.5%-5% of polyvinylidene fluoride; the negative electrode system of the lithium ion battery comprises the following components: 90%-95% of a graphite material, 2%-6% of a conductive agent, 1%-4% of sodium carboxymethyl cellulose, and 1%-4% of styrene-butadiene rubber.

8. The high temperature resistant and long life ternary lithium ion battery according to claim 1, characterized in that: The coating surface density of the positive electrode material is 28-32 mg / cm 2 The coating surface density of the negative electrode material is 14-17 mg / cm 2 .